Zeb2: Inhibiting the inhibitors in Schwann cells. Issue 1 (1st January 2017) - Brinkmann, Bastian G.; Quintes, Susanne
ABSTRACT: Development of Schwann cells is tightly regulated by concerted action of activating and inhibiting factors. Most of the regulatory feedback loops identified to date are transcriptional activators promoting induction of genes coding for integral myelin proteins and lipids. The mechanisms by which inhibitory factors are silenced during Schwann cell maturation are less well understood. We could recently show a pivotal function for the transcription factor zinc finger E-box binding homeobox 2 (Zeb2) during Schwann cell development and myelination as a transcriptional repressor of maturation inhibitors. Zeb2 belongs to a family of highly conserved 2-handed zinc-finger proteins and represses gene transcription by binding to E-box sequences in the regulatory region of target genes. The protein is known to repress E-cadherin during epithelial to mesenchymal transition (EMT) in tumor malignancy and mediates its functions by interacting with multiple co-factors. During nervous system development, Zeb2 is expressed in neural crest cells, the precursors of Schwann cells, the myelinating glial cells of peripheral nerves. Schwann cells lacking Zeb2 fail to fully differentiate and are unable to sort and myelinate peripheral nerve axons. The maturation inhibitors Sox2, Ednrb and Hey2 emerge as targets for Zeb2-mediated transcriptional repression and show persistent aberrant expression in Zeb2-deficient Schwann cells. While dispensible for adult Schwann cells, re-activation of Zeb2 is essential after nerve injury to allow remyelination and functional recovery. In summary, Zeb2 emerges as an "inhibitor of inhibitors, " a novel concept in Schwann cell development and nerve repair.